Zur Habenzinsbindung in den Vereinigten Staaten - Hartmut Schmidt (Kredit und Kapital, 1971)
On Deposit Rate Maintenance in the United States There have been maximum interest rates for deposits in the USA since the Thirties, but up to 1966 they affected only parts of the banking system, and only occasionally did interest on deposits rise to the maximum rates. Then, however, the scope of their applicability was extended; moreover, the maximum rates mostly no longer permitted fair market interest on deposits. Deposit rate maintenance, once introduced to protect the depositor and almost forgotten for two decades, was revived as an instrument of cyclical policy and credit control, and initially, it seemed, with some success. In order to avoid having to respond to massive withdrawals of now low-interest deposits by partial liquidation of assets, the banks sought and found ways of replacing deposits by other liabilities, if they had not already succeeded in preventing the outflow of funds by way of premiums and tie-in transactions. The supervisory authorities did not succeed ın blocking at an early date all the possible courses of evasive action that were adopted in the course of time and in enabling deposit rate maintenance to take full effect, to some extent probably because they did not want to disturb the structure of the credit markets even more. Anyhow, short-term direct credits recorded record growth rates, and many former depositors blindly waived the protection that lies in the intermediation of the banks. This became very obvious after Penn Central became insolvent. Credits were misdirected, forces of production were wasted in evasive processes, and there were unfavourable distributive effects which were not balanced by any evident successes. It is therefore hardly to be expected that interest rate maintenance will again attain the importance it had in recent years. For the German observer it is interesting for two reasons: It throws light on the debate concerning decontrol of interest rates in Germany, and it brought into being and favoured new forms of banking business.
Keywords: 330